Stylistic differences in male and female undergraduate narratives: A content analysis in an EFL context - Muhammad Alif Rizkiawan; Abu Bakar Razali; Mohammad Owen (Scientific English, 2025)
Writing skills are important for EFL learners, especially those in tertiary education where they are required to engage in English writing throughout their studies. While most English writing in tertiary education tends to be academic in nature, there are also narrative writings that are done by these students especially those who are majoring in English education or English literature. While there are many studies done on academic writing, there are few done on narrative writing. Therein the question lies as to if there are variations between male and female EFL students’ styles in narrative writing, which might influence how these writings are perceived or even evaluated. Therefore, this study is conducted to probe into stylistic variations between male and female undergraduate learners in their EFL character-based narrative writing. It employed descriptive qualitative methodology by way of document-based analysis. The stylistic features framework introduced by Rubin and Greene (1992) was used to distinguish writing styles between male and female undergraduate EFL students. It was found that female students applied majority of 13 stylistic features while writing which consisted of different connectives and pronouns with intensifiers alongside de-intensifiers and proximals and auxiliaries of possibility plus demonstratives. This led to more coherent and expressive writing style. The expressions of moral lessons from male students appeared shorter and indirect while female students' responses were both thorough and clear conclusions. The study proves that gendered language patterns in EFL writing tasks remain dominant thus generating implications for teaching approaches which support different writing approaches.